Developing STEM project-based learning module for primary school teachers: a need analysis - Septiadevana, Riski; Abdullah, Norazilawati (Institute of Advanced Engineering and Science, 2024)
The integration of science, technology, engineering, and mathematics (STEM) with project-based learning is beneficial in facilitating students to compete effectively in the 21st century, but teachers still encounter obstacles, so in implementation, especially in primary schools, is still rarely done. Therefore, it is necessary to develop STEM project-based learning module to overcome teacher problems. This study aims to collect and analyze teacher perspectives regarding their requirements for the development of STEM project-based learning module. This study was conducted using a design and developmental research (DDR) approach. The first phase included need analysis, carried out through an online questionnaire. The participants consisted of 397 teachers in Cirebon and the results showed that primary school teachers required STEM project-based learning module to facilitate the development of relevant skills in the 21st century, such as scientific literacy and critical thinking. Based on the data collected, the most difficult topic and the topic with the highest forms of misconceptions appeared to be human body organ systems, with a percentage value of 21.16% and matter and change, with a percentage at 21.41%. STEM project-based learning module for primary school level can be developed for various topics such as human body organs or matter and changes.